In-depth investigation into the binding capabilities of palladium-based N-heterocyclic carbenes towards five heavy metals: Hg, Cd, Pb, Cr, and As - Qiao Liu; Xianghe Kong; Qian Ru Li; Wenbo Lan (PLoS ONE, 2025)
Given the severe environmental and health risks posed by heavy metal pollutants such as mercury (Hg), cadmium (Cd), lead (Pb), chromium (Cr), and arsenic (As), the development of highly efficient and selective capture materials is critically important.This study explores the molecular structural characteristics of complexes formed by substituting the central palladium atom in nitrogen-heterocyclic carbene complexes with mercury (Hg), cadmium (Cd), lead (Pb), chromium (Cr), and arsenic (As). For all the complexes, the simulated infrared and ultraviolet-visible spectra, Wiberg bond indices, as well as the binding ability of nitrogen-heterocyclic carbene ligands to the central atom were assessed. The results show that the complexes obtained when the central atom is replaced by Hg, Cd, Pb, Cr, or As are stable and display unique spectral features. Significantly, nitrogen-heterocyclic carbene has the strongest binding affinity for Pd. The complexes of chromium substitutes possess relatively high chemical stability. These findings will offer important references for future pollution control and support the specific capture of the five studied heavy metals, and enrichment of Cr using nitrogen-heterocyclic carbene ligands.